(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines technologies for implementing a dialogic approach in the educational process, with an emphasis on preparing political science students. It analyzes the philosophical and pedagogical foundations of dialogic pedagogy and contemporary research in the field of dialogic learning. Particular attention is paid to practical methods: the Socratic (question-dialogic) method and project-based learning (PBL), including examples of their application in political science education. It is shown that the implementation of dialogic technologies promotes the development of critical and metacognitive thinking, communicative and teamwork competencies, and also fosters independent and reflective student attitudes.